"It's complicated...": Exploring second stage caesarean sections and reasons for non-performance of assisted vaginal births in Kenya: A mixed methods study. - Fiona M Dickinson; Helen Allott; Paul Nyongesa; Martin Eyinda; Onesmus M Muchemi; Stephen W Karangau; Evans Ogoti; Nassir A Shaban; Pamela Godia; Lucy Nyaga; Charles A Ameh (Public Library of Science (PLoS), 2023)
Unnecessary Caesarean Section (CS) can have adverse effects on women and their newborns. Assisted vaginal birth/delivery (AVB/AVD) using a suction device or obstetric forceps is a potential alternative when delays or complications occur in the second stage of labour. Unlike CS, AVB using a suction device does not require regional or general anaesthesia, can often be performed by midwives, and does not scar the uterus, lowering the risk of maternal mortality and morbidity, in this and subsequent pregnancies. This study examined the appropriateness and outcomes of second stage CS (SSCS), and reasons for low levels of AVB use, in Kenya. Using a mixed methods study design, we reviewed case notes from women having SSCS births and AVB, and conducted key informant interviews with healthcare providers, from 8 purposively selected hospitals in Kenya. Randomly selected SSCS and all AVB case notes were reviewed by a panel of four experienced obstetricians, and appropriateness of the procedure assessed. Semi-structured interviews were conducted with obstetricians, medical officers and midwives, and analysed using a thematic approach. Review of 67 SSCS case notes showed 10% might have been conducted as AVBs, with a further 58% unable to be classified due to inadequate/inconsistent record keeping or excessive delay following initial CS decision. Outcomes following SSCS showed perinatal mortality rate of 89.6/1,000 births, with 11% of infants and 9% of mothers experiencing complications. Non-referred cases of AVB showed good outcomes. The findings of the 20 interviews explored the experience and confidence of healthcare providers in performing AVBs, and adequacy of the training they received. Key reasons for non-performance included lack of functioning equipment, lack of trained staff or their rotation to other departments. Reasons for non-performance of AVB were complex and often multiple. Any solutions to these problems will need to address various local, regional and national issues.